2012
DOI: 10.1016/j.devcel.2012.09.021
|View full text |Cite
|
Sign up to set email alerts
|

The NF-κB Signaling Protein Bcl10 Regulates Actin Dynamics by Controlling AP1 and OCRL-Bearing Vesicles

Abstract: The protein Bcl10 contributes to adaptive and innate immunity through the assembly of a signaling complex that plays a key role in antigen receptor and FcR-induced NF-κB activation. Here we demonstrate that Bcl10 has an NF-κB-independent role in actin and membrane remodeling downstream of FcR in human macrophages. Depletion of Bcl10 impaired Rac1 and PI3K activation and led to an abortive phagocytic cup rich in PI(4,5)P(2), Cdc42, and F-actin, which could be rescued with low doses of F-actin depolymerizing dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 50 publications
2
91
0
3
Order By: Relevance
“…on May 12, 2018. by guest www.bloodjournal.org From Impaired dectin-1-mediated Rac1 activation and phagocytosis in XIAP-deficient macrophages BCL10 was recently shown to participate in Rac1 activation, F-actin remodeling, and phagosome closure that are independent of NF-kB activation. 47 We found that curdlan-induced Rac1 activation was attenuated in Xiap 2/2 BMDMs (supplemental Figure 10A). Similarly, dectin-1-induced Rac1 activation was impaired in XIAPknockdown human macrophages ( Figure 6A).…”
Section: Xiapmentioning
confidence: 84%
“…on May 12, 2018. by guest www.bloodjournal.org From Impaired dectin-1-mediated Rac1 activation and phagocytosis in XIAP-deficient macrophages BCL10 was recently shown to participate in Rac1 activation, F-actin remodeling, and phagosome closure that are independent of NF-kB activation. 47 We found that curdlan-induced Rac1 activation was attenuated in Xiap 2/2 BMDMs (supplemental Figure 10A). Similarly, dectin-1-induced Rac1 activation was impaired in XIAPknockdown human macrophages ( Figure 6A).…”
Section: Xiapmentioning
confidence: 84%
“…[62][63][64] A similar mechanism was proposed to explain defects in fluid phase uptake observed in LS patient fibroblasts as compared to normal cells. 56 …”
Section: Phagocytosis and Macropinocytosismentioning
confidence: 93%
“…La PI3 kinase et la phospholipase C sont impliquées dans la réduction de la quantité de PI(4,5)P 2 [2]. Nous avons montré que la phosphatase OCRL (oculocerebrorenal syndrome of Lowe) contribue également à l'hydrolyse de PI(4,5)P 2 lors de la phagocytose [17], et au moment de l'abscission durant la cytocinèse [18]. Par ailleurs, la cofiline, une protéine de fragmentation des filaments d'actine polymérisée, est recrutée aux coupes phagocytaires, et son activité est régulée par la kinase LIM [19].…”
Section: Dynamique De Polymérisation Et Dépolymérisation De L'actineunclassified
“…De plus, Rab35 régule l'hydrolyse de PI(4,5)P2 et, donc, le remodelage de l'actine, via la localisation de la phosphatase OCRL dans les ponts intercellulaires avec la membrane plasmique, a d'abord été développé dans le contexte de la formation du phagosome [28,29]. Plus récemment, nous avons montré que le trafic vésiculaire était concentré à la base du phagosome en formation, et non pas dans les pseudopodes en extension [17]. L'apport vésiculaire est requis pour la stabilité des ponts intercellulaires et pour l'abscission [30,31].…”
Section: Régulateurs Du Trafic Membranaireunclassified
See 1 more Smart Citation